GPR97 deficiency ameliorates renal interstitial fibrosis in mouse hypertensive nephropathy - Wu Ji-chao; Wang Xiao-jie; Zhu Jing-han; Huang Xue-ying; Liu Min; Qiao Zhe; Zhang Yan; Sun Yu; Wang Zi-ying; Zhan Peng; Zhang Tao; Hu Hui-li; et al. (Acta Pharmacologica Sinica; Vol 44, No 6 (June 2023): Acta Pharmacologica Sinica, 2023)
Hypertensive nephropathy (HTN) ranks as the second-leading cause of end-stage renal disease (ESRD). Accumulating evidence suggests that persistent hypertension injures tubular cells, leading to tubulointerstitial fibrosis (TIF), which is involved in the pathogenesis of HTN. G protein-coupled receptors (GPCRs) are implicated in many important pathological and physiological processes and act as important drug targets. In this study, we explored the intrarenal mechanisms underlying hypertension- associated TIF, and particularly, the potential role of GPR97, a member of the adhesion GPCR subfamily, in TIF. A deoxycorticosterone acetate (DOCA)/salt-induced hypertensive mouse model was used. We revealed a significantly upregulated expression of GPR97 in the kidneys, especially in renal tubules, of the hypertensive mice and 10 patients with biopsy-proven hypertensive kidney injury. GPR97−/− mice showed markedly elevated blood pressure, which was comparable to that of wild-type mice following DOCA/salt treatment, but dramatically ameliorated renal injury and TIF. In NRK-52E cells, we demonstrated that knockdown of GPR97 suppressed the activation of TGF-β signaling by disturbing small GTPase RhoA-mediated cytoskeletal reorganization, thus inhibiting clathrin-mediated endocytosis of TGF-β receptors and subsequent Smad activation. Collectively, this study demonstrates that GPR97 contributes to hypertension-associated TIF at least in part by facilitating TGF-β signaling, suggesting that GPR97 is a pivotal intrarenal factor for TIF progression under hypertensive conditions, and therapeutic strategies targeting GPR97 may improve the outcomes of patients with HTN.